The The effect of Prenatal Yoga Exercise on the back pain of pregnant women in 3rd trimester In The Kampung Jabi Health Centre Batam City - Hidayah, Nurul; Pramita Sari , Desi; Nur Rosyidah, Haqqelni (Yayasan Inspirasi El Burhani, 2025)
Introduction: Back pain was a common disorder which occured in pregnancy,pregnant women might have had a history of previous back pain. In order to overcome back pain could be done by yoga gymnastics which which was beneficial to form a strong posture, purifying the central nerves found in the spine.Objective: This reseach aimed to know the effect of Prenatal Yoga Exercise on the back pain of pregnant women in 3rd trimester In The Kampung Jabi Heatlh Centre, Sub-District Of Nongsa, Batam City. Method: This research type was pre-experimental with the design of two group pretest posttest design. The populationsof this research were all third trimester pregnant In The Kampung Jabi HeatlhCentre, Sub-District Of Nongsa, Batam City which amounted to 51 pregnant women. The samples were 45 pregnant women which were taken by purposive sampling. The independent variable was yoga gymnastics and the dependent variable was back pain of pregnant women in 3rd trimester. The research instrumen used a questionnaire. Data processing used editing, coding, scoring,tabulating with data analysis of spearman Rank. Result: The research resultshowed that’s before being conducted Prenatal Yoga Exercise almost a half of pregnant women experienced back pain with scale 2 (a little more pain) as many as 44,4% with 20 respondent while after being conducted Prenatal Yoga Exercise almost a half of pregnant women experienced back pain with scale 1 (little pain) as many as 48,9% with 22 respondent. The statistical test of Spearman rank showedthat’s value = 0,001 < α (0,05) so H1 was accepted. Conclusion: There is an effect of Prenatal Yoga Exercise on the back pain of pregnant women in 3rd trimeste. It was expected for pregnant women to follow if there would be yoga gymnastics, which would be useful to overcome back pain, if there are not pragnant women can do self at home. Keywords : back pain of pregnant prenatal yoga exercise, 3rd Trimester